Managing the Past into Future: Materiality and Discourse on Cultural Landscape - Widjaja Martokusomo; Budi Faisal; Huda Nurjanti; Feysa Poetry; Nathania Nadia (Journal of Infrastructure & Facility Asset Management, 2022)
Referring to the understanding of landscape as a cultural construct, the notion of the cultural landscape is constituted by its essential elements: system, people, and the landscape itself. The nexus between these elements was philosophically developed in a recent discourse that challenges the separation between cultural and natural heritage. This "segregation" is based originally on the hegemony of western values, in which cultural heritage resides mainly in monuments and sites; meanwhile, natural heritage is formed by the scientific idea of nature and wilderness as something isolated from people.The landscape of Muara Muntai, a tiny settlement that has grown and developed on the riparian of Mahakam River, is characterized by the use of Ironwood or Eusideroxylon zwageri Teijsm (locally known as Kayu Ulin). This native plant of East Kalimantan is considered noteworthy, and in the perspective of ecology, is currently categorized as "threatened" due to deforestation in the last decades. For a couple of hundred years, locally-sourced Ironwood has been purposed and processed autonomously by the community as building and linkage-system material, creating a unique ambiance for Muara Muntai. The so-called modernization significantly changes the value of this native material: Ironwood building façades have been renovated into brick cement for the sake of practicality; Ironwood roads and bridges have been gradually paved with concrete to make way for motorized transportation.Noting that the spirit of the place resides as much in the meaning and symbolism of place as it does in the locus settings, it requires a holistic approach to understand the conflict between modernization and place identity. The case of Muara Muntai will showcase how values of cultural heritage and its attributes -also to what extent the integrity, i.e. wholeness and intactness-will be able to be read and interpreted to give an overall sense of continuity.